Segmentation characteristics of strike-slip fault zone and its reservoir control mechanisms in the southwestern Tarim Basin - Guo, Jialiang; Yang, Ruizhao; Geng, Feng; Wang, Li; Zhang, Shijie; Wang, Lingda; Han, Fengtao (Frontiers in Earth Science, 2024)
Understanding how fault-related structures influence oil and gas accumulation is crucial for geological investigations and exploration planning. This study, based on 3D seismic data, analyzes the northeast-trending strike-slip fault zone in the eastern part of the Bachu Uplift. Automatic fault extraction techniques were employed to delineate the strike-slip fault zone, and the parallel bedding indicator was used to identify reservoirs and investigate the fault’s segmented features and reservoir-controlling characteristics. The results show that the northeast-trending strike-slip fault is primarily governed by simple shear stress and conforms to the Riedel shear model. Three distinct structural styles were developed: vertical, pull-apart, and push-up segments, each exhibiting varying profile characteristics and planar patterns. The segmentation of the strike-slip fault controls the distribution of Ordovician fault-karst reservoirs. An oil and gas enrichment model for the strike-slip fault zone has been established, characterized by external hydrocarbon supply, fault-mediated migration, segmented reservoir control, and high-elevation accumulation. This study offers valuable insights for the exploration of fault-karst reservoirs controlled by strike-slip faults.